2013
DOI: 10.1176/appi.ajp.2012.12040454
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Prolonged Fatigue in a U.S. Sample of Adolescents

Abstract: These findings suggest that prolonged fatigue is associated with disability and is an important clinical entity independent of mood and anxiety disorders in adolescents. Persistent fatigue with a comorbid mood or anxiety state is related to even more functional impairment, suggesting that prolonged fatigue may reflect greater severity of mood and anxiety disorders in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…Tension type headaches and chronic daily headaches in our study are also more common than the 10– 25 % and 3.5 % reported in adolescents [24, 25]. The prevalence of fatigue in our cohort is similar to that reported in ALL survivors and more than that reported in healthy adolescents [26, 27]. We found neuropathy to be less prevalent than that reported by Ramchandren et al but they had only 37 ALL survivors in their cohort [28].…”
Section: Resultssupporting
confidence: 85%
“…Tension type headaches and chronic daily headaches in our study are also more common than the 10– 25 % and 3.5 % reported in adolescents [24, 25]. The prevalence of fatigue in our cohort is similar to that reported in ALL survivors and more than that reported in healthy adolescents [26, 27]. We found neuropathy to be less prevalent than that reported by Ramchandren et al but they had only 37 ALL survivors in their cohort [28].…”
Section: Resultssupporting
confidence: 85%
“…Fatigue has also been associated with lower cortisol responses to stress in non-depressed adults (Lennartsson et al, 2015). Understanding the mechanisms linking fatigue and blunted cortisol reactivity is critical given that depressed adolescents with prolonged fatigue exhibited greater disability and health service use than adolescents with either prolonged fatigue or depression alone (Lamers et al, 2013). The relative impact of insomnia versus hypersomnia and increased versus decreased appetite on cortisol responses could not be addressed because all symptoms were included in the neurovegetative composite.…”
Section: Discussionmentioning
confidence: 99%
“…7 Chronic fatigue of at least 3 months' duration affects 2% to 3% of children and young people aged 8 to 18 years. [8][9][10] Population-based studies in the United Kingdom and the United States have reported a prevalence of 1.3% for fatigue of ≥6 months' duration. 8,9,11 Although clinician-verified CFS seems to be less prevalent (0.1%-0.5%), [12][13][14] this discrepancy is almost certainly a consequence of referral pathways and barriers to accessing clinical services.…”
mentioning
confidence: 99%